Role and Clinical Significance of Plasma N-Terminal Brain Natriuretic Peptide Measurement in Children with Brain Edema - Taskesen, Mustafa; Celik, Hasan; Yaramis, Ahmet; Tas, Mehmet A. (Neuropediatrics, 2016)
Objective Brain natriuretic peptide (BNP) is a potent natriuretic and vasodilator factor. BNP plasma concentrations were found to be elevated in patients with brain edema. The purpose of the present study is to evaluate the relationship between plasma NT-proBNP concentration and the presence of brain edema in patients with intracranial pathology.Materials and Methods The plasma NT-proBNP levels of 50 patients and 25 healthy subjects were measured. The NT-proBNP levels of the patient group were measured during admission and after 7 days of treatment.Results NT-proBNP plasma concentrations were found to be significantly higher in the patient group with brain edema than in the control group (p < 0.005). There were no significant differences in the NT-proBNP plasma concentrations between patients with intracranial pathology without brain edema and the control group (p > 0.005). NT-proBNP plasma concentrations were found to be significantly higher in patients with brain edema as compared with patients without brain edema before treatment (p < 0.005).Conclusion These results suggest that excessive secretion of plasma NT-proBNP is related to brain edema. Plasma NT-proBNP levels may serve as a marker to guide the early-diagnostic and therapeutic management in children with brain edema. Further studies are required to evaluate the role of BNP in brain edema pathophysiology.
Keywords: brain edema; NT-proBNP; children